1993
DOI: 10.1002/j.1460-2075.1993.tb06176.x
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal T cell development in CD3-zeta-/- mutant mice and identification of a novel T cell population in the intestine.

Abstract: The T cell antigen receptor (TCR)‐associated invariable membrane proteins (CD3‐gamma, ‐delta, ‐epsilon and ‐zeta) are critical to the assembly and cell surface expression of the TCR/CD3 complex and to signal transduction upon engagement of TCR with antigen. Disruption of the CD3‐zeta gene by homologous recombination resulted in a structurally abnormal thymus which primarily contained CD4‐ CD8‐ and TCR/CD3very lowCD4+CD8+ cells. Spleen and lymph nodes of CD3‐zeta‐/‐ mutant mice contained a normal number and rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
115
2

Year Published

1994
1994
2003
2003

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 176 publications
(127 citation statements)
references
References 75 publications
10
115
2
Order By: Relevance
“…It is known that the´chain plays a critical role during thymocyte development [6,36,37]. Although the immunoreceptor tyrosine-based activation motif (ITAM) of thé chain may not be absolutely required for the development of T cells, the number of ITAM correlates with the efficiency of thymocyte selection in vivo [38].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It is known that the´chain plays a critical role during thymocyte development [6,36,37]. Although the immunoreceptor tyrosine-based activation motif (ITAM) of thé chain may not be absolutely required for the development of T cells, the number of ITAM correlates with the efficiency of thymocyte selection in vivo [38].…”
Section: Discussionmentioning
confidence: 99%
“…The DOTCR + T cells are selected by the MHC class II I-A d molecules and they also can interact with I-A b molecules [6,20]. It has been shown that DOTCR is expressed predominantly on CD4 + CD8 -T cells bearing conventional TCR complex in H-2 d mice (DOTG dd mice) [21].…”
Section: Altered Development Of Cd4 + Dotcr + T Cells Bearing Alternamentioning
confidence: 99%
See 3 more Smart Citations